Directive Leadership Style as a Mediator of Work Environment and Organizational Commitment Influences on Job Satisfaction - Ike Diyah Pravitasari; Dewie Tri Wijayanti Wardoyo; Andre Dwijanto Witjaksono (Universitas Pendidikan Indonesia, 2025)
Since 2022, there has been a change in the Organizational Structure and Work Procedures (also called as SOTK) in the Regional Apparatus Organization of Surabaya City, which has transferred the responsibility for the rehabilitation of school building facilities, infrastructure, and utilities from the Public Housing Service to the Education Service. This change also caused the transfer of 154 contract workers with the positions of craftsmen and assistant craftsmen to the Education Service. This study aims to analyse the influence of the work environment and organizational commitment on job satisfaction, with directive leadership style as a mediating variable. Data were analysed using the Structural Equation Model (SEM) with the help of SEM with smartPLS software. The research sample consisted of 61 respondents selected from 154 members of the Education Service task force through the stratified sample method. The results show that the questionnaire instrument is valid and reliable. The work environment and organizational commitment have a significant positive influence on job satisfaction, but directive leadership style is not proven to mediate this influence on the Surabaya City Education Service task force.